Can the EU's Arctic policy find a true north? - Stępień, Adam; Raspotnik, Andreas (2019)
Disappearing Arctic ice and thawing permafrost are making international headlines alongside burning forests. Moreover, increased international attention is currently focused on the Arctic because of China’s regional interests, Russia’s militarisation efforts, tweets from a particularly polarising US President and controversial statements by his Secretary of State. These Arctic changes have ripple effects on Europe, be it rising sea levels, coastal flooding, changing weather patterns, or through the significance of regional economic changes. What should the European Union do about these developments? Is there a need for an update of its Arctic policy? An ambivalent policy of fence-sitting that is currently lacking a long-term perspective, clear goals and necessary financial support mechanisms, the EU’s Arctic approach requires simplification. The EU’s Arctic engagement needs to be future-oriented, with clearly stated goals and an honest assessment of what the EU can and wants to achieve in the Circumpolar North.